Side chain polysiloxanes with phthalocyanine moieties - T. Ganicz; T. Makowski; W. A. Stanczyk; A. Tracz (eXPRESS Polymer Letters, 2012)
Side chain polysiloxane with 5-(pentyloxy)-3-methyloxy-9,10,16,17,23,24-hexakis(octenyloxy)phthalocyanine moieties is synthesized by hydrosilylation reaction. The phase behavior and thermooptical properties of the polysiloxane and starting 2-(pent-4-enyloxy)-3-methyloxy-9,10,16,17,23,24-hexakis(octenyloxy)phthalocyanine is examined by POM (Polarizing optical microscopy), TOA (thermooptical analysis), DSC (differential scanning calorimetry), AFM (atomic force microscopy) and SAXS (small angle X-ray scattering) studies. The effect of the attachment of phthalocyanine to polysiloxane chains over phase transitions and phase morphology is discussed in details.